2021
DOI: 10.3390/e23070797
|View full text |Cite
|
Sign up to set email alerts
|

Bell Diagonal and Werner State Generation: Entanglement, Non-Locality, Steering and Discord on the IBM Quantum Computer

Abstract: We propose the first correct special-purpose quantum circuits for preparation of Bell diagonal states (BDS), and implement them on the IBM Quantum computer, characterizing and testing complex aspects of their quantum correlations in the full parameter space. Among the circuits proposed, one involves only two quantum bits but requires adapted quantum tomography routines handling classical bits in parallel. The entire class of Bell diagonal states is generated, and several characteristic indicators, namely entan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
(132 reference statements)
0
17
0
Order By: Relevance
“…A statistical mixture of these pure quantum states is called a BDS. Despite their simple structure, BDSs play a crucial role in the theory of quantum information [34], because they form a representative three-dimensional subspace of the full 15-dimensional space of two-qubit mixed states. The two-qubit state is a BDS iff r = s = 0.…”
Section: Solution Of the Master Equationmentioning
confidence: 99%
“…A statistical mixture of these pure quantum states is called a BDS. Despite their simple structure, BDSs play a crucial role in the theory of quantum information [34], because they form a representative three-dimensional subspace of the full 15-dimensional space of two-qubit mixed states. The two-qubit state is a BDS iff r = s = 0.…”
Section: Solution Of the Master Equationmentioning
confidence: 99%
“…It has shown that quantum computers can solve a range of algorithms and complex protocols that conventional computers cannot. [ 31 ] Non‐local features, such as non‐classical correlation, non‐locality, and entanglement, are required by such quantum computers and related technology, [ 32,33 ] therefore, will remain the primary focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…The accompanying open source Qiskit software [4] allows to compare simulation of any algorithm run on this software and the actual IBM quantum device, hence assessing the level of noise and gate imperfections and their effect on the output of any algorithm. Quite recently this has led many groups to run interesting algorithms on this quantum computer with promising results [5][6][7][8][9][10][11][12][13][14]. Among these works, the ones which have inspired our work are the study of a class of two-qubit states, namely Bell diagonal and Werner states, specially with regard to their correlation properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently this has led many groups to run interesting algorithms on this quantum computer with promising results [5][6][7][8][9][10][11][12][13][14]. Among these works, the ones which have inspired our work are the study of a class of two-qubit states, namely Bell diagonal and Werner states, specially with regard to their correlation properties [9,10]. These are classical mixtures of the form,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation